RISE: An outlook on sustainability in medicine and beyond / Professor Dr Hapziah Md Nawawi - Md Nawawi, Hapziah (Office of the Deputy Vice-Chancellor (Research & Innovation), 2022)
A renowned expert in Atherosclerosis, Familial Hypercholesterolaemia (FH) and Heart Disease Prevention, Professor Datin Dr Hapizah Md Nawawi, Founding Director and Principal Fellow, Institute of Pathology, Laboratory and Forensic Medicine (I-PPerForM), spoke eloquently about sustainability in medicine, and the meaning of the terminology in broader and various other contexts. "In science, sustainability refers to the dynamic interaction between science and art, in ways that do not destroy nature. When we talk about sustainability and medicine, it would refer to efforts to coordinate, sustainable practices, and improving patient outcomes. This is also consistent with the notion of a sustainable healthcare system according to WHO, which aims at improving, maintaining, and restoring health with minimal impact to the future generation.